Analysis Factors Causing the Occurrence of Free Sex in Banjarmasin - Topan, R. Topan Aditya Rahman; Yuandari, Esti (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2021)
Adolescents are human resources with high potential, their awareness of reproductive health is important to grow. Adolescents, along with their development, begin to explore with themselves, the values, identity, roles and behavior. In addition, free sex has a great opportunity for adolescents to marry early, contract sexually transmitted diseases and HIV-AIDS. Based on the contributing factors, what can encourage adolescents to have free sex are internal and external factors. The internal factor is lack of knowledge about sex or wrong and high curiosity. Meanwhile, the external factor is the stimulation of pornography through the media of information technology and the influence of peers. In this study, using a qualitative approach, the results obtained on the factors that cause free sex in adolescents are more detailed, clearer and more accurate